The comfort women of Iloilo, 1942-1945. - Lictawa, Francis Djholan D.
This is a pioneering study about the comfort women of Iloilo from 1942 to 1945. It aims to: (1) identify the comfort women of Iloilo and to establish the background and circumstances leading to their enslavement, (2) identify and locate the comfort houses of Iloilo, (3) describe the operation including the rules and regulations governing the comfort system, (4) determine how the Iloilo comfort women were treated during their enslavement in terms of their food ration, physical treatment, health and medication, and (5) ascertain the significance of the study to Iloilo's local history., The study used interview guides to the comfort women and other informants who have knowledge about the comfort system. It also utilized materials from books, old newspapers, magazines and data from Lila-Pilipina, a non-governmental organization of former sex slaves and concerned women. There were four Ilonggo comfort women who made their stories public. Like the Korean and Taiwanese women forced to the system, they were at their teens at the time of their conscription. As comfort women, they were held as sex slaves and sometimes tasked to prepare food and do laundry jobs. It was also found out that there were eight comfort stations in Iloilo province, six of which were located in Iloilo City. Visiting hours, fees for sexual service, maintenance and restrictions while inside the comfort station were covered by the rules and regulations that govern the operation of the comfort system. In addition to the revelations on the violations committed against women's rights during World War II, the study also includes the latest facts about the continuing struggle of the comfort women for their demands such as compensation from Japanese government. The study, therefore, is an attempt to mainstream women's stories in local history which have long been ignored by past historians.